The impact of financial development on private investment in South Africa - Hashikutuva, Lovisa Ndapewelao (Research of GSB, 2017)
The study analysed the impact of financial development (measured by depth, stability, efficiency and access) on private investment in South Africa over the period 1977 (Q1) to 2015 (Q4). Autoregressive distributive lag model was used in addition to conducting further tests to establish the efficiency of the model using standard diagnostics which confirmed the overall significance of the model. The results find the relationship between financial development and private investment in South Africa to be long-run in nature. The statistically significant variables found to explain the variance of private investment for South Africa in both the short- and long-run are market capitalization, domestic credit, growth in output as well as trade openness. Interest rate spread was found significant only in the short-run.